Kerkgeskiedskrywing: Hoe skryf ons kerkgeskiedenis? - Pont, A. D. (Hervormde teologiese studies, 1998)
Every generation writes its own history of the Church. As the past is continually evaluated from different points of view and as every generation asks new questions, so the understanding of the past changes and history is rewritten. In discussing this situation, three issues are treated: the understanding of the past and what history is, the requirements for writing history and the question whether history has a vision for the future. These matters continually appear in discussions on history and the requirements for writing history.